Investigating factors that affect willingness to pay: An analysis on freemium social media apps - Faria, A. M.; Dias, Á.; Pereira, L. F.; Lopes da Costa, R.; Gonçalves, R. (International Journal of Advanced Media and Communication, 2024)
Although social networks have grown in popularity and usage in recent years, little is known about users' willingness to pay (WTP) for the premium version. We investigate how consumers' perceived value is associated with their intention to use freemium services and to purchase premium content. The data was collected through an online survey among users of freemium social media networks such as LinkedIn, YouTube, Reddit, and Flickr and was modelled using structural equations (SEM). The results reveal that users who value the security component in freemium social networks will have a higher intention to use the service and that the price value of freemium services is shown to have a negative association with the intention to purchase premium content. The perceived value of the service, improved security, or increased frequency of use can impact future profitability through increased retention on the one hand and reduced monetisation on the other.